2005
DOI: 10.1097/01.all.0000173783.42906.95
|View full text |Cite
|
Sign up to set email alerts
|

Bee venom allergy in beekeepers and their family members

Abstract: Beekeepers and their family members are at an increased risk of severe sting anaphylaxis and therefore need especially careful instruction with regard to avoidance of re-exposure, emergency treatment and specific immunotherapy with bee venom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 30 publications
2
70
1
2
Order By: Relevance
“…These figures have to be interpreted cautiously, however, as we cannot be completely sure that patients recalled correctly when they had been re-stung. For a long time, beekeepers and their family members have been identified as a high-risk group of hymenopteravenom-allergic patients, and management options for this population have already been adapted, recommending VIT not only to beekeepers suffering from mild grade I and grade II systemic allergic reactions, but even to those suffering from repeated large local reactions [23] . However, the majority (63%) of bee-venom-allergic patients do not belong to this high-risk group and only face a small risk of being re-stung.…”
Section: Discussionmentioning
confidence: 99%
“…These figures have to be interpreted cautiously, however, as we cannot be completely sure that patients recalled correctly when they had been re-stung. For a long time, beekeepers and their family members have been identified as a high-risk group of hymenopteravenom-allergic patients, and management options for this population have already been adapted, recommending VIT not only to beekeepers suffering from mild grade I and grade II systemic allergic reactions, but even to those suffering from repeated large local reactions [23] . However, the majority (63%) of bee-venom-allergic patients do not belong to this high-risk group and only face a small risk of being re-stung.…”
Section: Discussionmentioning
confidence: 99%
“…131 This may be a result of true double-sensitization, or cross-reactivity between bee and vespid venom protein allergens (hyaluronidase has about 50% sequence homology), or cross-reacting CCDs. Inhibition tests with both venoms and CCDs using RAST inhibition or immunoblot have been used to distinguish between doublesensitization and cross-reactivity, 125,126,131,132 which is important for the selection of venoms for immunotherapy.…”
Section: Risk Assessment In Individuals With Hymenoptera Venom Allergymentioning
confidence: 99%
“…Recent studies have shown that bee-keepers, despite being frequently stung and having a positive skin-prick test and IgE specific to bee venom, do not develop allergic symptoms when stung. Protection seems to be mediated through the induction of bee venom-specific IgG4 following bee stings, since long-term exposure to bee stings drives the IgG response from a mainly IgG1 response to an IgG4 response (Muller 2005), although an in vivo switch to IL-10-secreting T regulatory cells has also recently been implicated in this process (Meiler et al 2008). In addition to IgG, recent studies have also provided evidence for increases in the amount of TGF-b-driven allergen-specific IgA following SIT, indicating that other antibody classes might contribute to clinical efficacy (Pilette et al 2007).…”
Section: Roles Of Other Immunoglobulins In Allergymentioning
confidence: 99%